Adverse event profile of albumin-bound paclitaxel: a real-world pharmacovigilance analysis - Duan, Yuanqiong; Wang, Ying; Lu, Shentao; Zeng, Mei; Liu, Lubin; Dai, Qian; Yin, Rutie (Frontiers in Pharmacology, 2024)
Abraxane plays a crucial role in the treatment of various types of cancer, despite the considerable attention it has garnered for its adverse drug events (ADEs).Nevertheless, there is currently a significant lack of comprehensive real-world pharmacovigilance studies on the ADEs associated with Abraxane.We conducted a retrospective analysis of ADEs associated with Abraxane using data mining from the FAERS database, analyzing data from 2005 to 2023. In a realworld setting, we quantified and visualized the signals of these ADEs using four pharmacovigilance algorithms.The FAERS database identified a total of 10,230 adverse event reports associated with Abraxane. The study revealed that Abraxane-related adverse drug events involved 27 system organ classes (SOC), with the strongest signals associated with the lymphatic and hematological systems and hepatobiliary disorders. Additionally, we identified 70 significant Preferred Terms (PT) signals, which included some critical adverse events not highlighted in the product labeling, such as cystoid macular edema. Further analysis of the timing of adverse reactions showed a median onset time of 41 days. Most adverse events (AEs) occurred within the first month of using Abraxane (43.5%), although some were still possible one year after treatment (3.5%).Gender-specific analysis indicated that high-risk AEs differed between females (nausea, vomiting, and erythema) and males (febrile neutropenia, disseminated intravascular coagulation, and upper gastrointestinal bleeding).The examined results provide crucial recommendations for optimizing the administration of Abraxane, enhancing its effectiveness, and mitigating potential adverse effects. This knowledge will substantially facilitate the implementation of the substance in clinical settings.